PENGARUH PENGGUNAAN METODE BELAJAR BLENDED LEARNING TERHADAP MOTIVASI BELAJAR MAHASISWA DI MASA PANDEMI COVID-19 - Henrianto Karolus Siregar; Elvipson Sinaga; Khairunnisa Batubara; Romauli Ervannya Goria Siallagan; Sri Wahyuni Siregar (Jurnal Keperawatan Priority, 2023)
The impact of the COVID-19 pandemic that occurred in Indonesia caused the learning process in tertiary institutions to change. The learning process in tertiary institutions is required to be mastered in their respective homes. This has an impact on the learning process activities on campus which has 45.5 million students and students are one of the places prone to the spread of the COVID-19 virus. This study aims to determine the effect of using blended learning methods on student motivation in medical-surgical nursing courses during the COVID-19 pandemic. This type of research uses quantitative research with a cross-sectional design approach. The population in this study were all nursing diploma students totaling 160 people. The sample used was purposive sampling in which a sample determination technique was carried out by selecting a sample among the population according to what the researcher wanted as many as 67 people. This research was conducted in June-July 2022. Based on the results of the research conducted, it was found that there was an effect of using the blended learning method on student learning motivation in medical-surgical nursing courses during the COVID-19 pandemic with a p-value of 0.000. The use of blended learning methods can affect student learning motivation. The results of this study are expected to increase student motivation in attending lectures, especially medical-surgical nursing courses.